GAMBARAN DERAJAT NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III - Ella Khairunnisa; Eka Riana; Dwi Khalisa Putri; Sella Ridha Agfiani (WOMB Midwifery Journal, 2022)
Pregnancy brings physical and psychological changes which can cause discomfort, especially in the third trimester, such as frequent urination, breathing problems, back pain, difficulty defecating, difficulty sleeping, dyspnea, discomfort in the perineum, leg muscle cramps, varicose veins, edema in the legs, fatigue, mood changes, and anxiety. The problem of back pain during pregnancy often occurs, especially in the 3rd trimester. Low back pain during pregnancy has an impact on the psychological, social life, and quality of life of pregnant women. This study aims to determine the characteristics and degree of back pain in third trimester pregnant women. This research is a descriptive research and has been done on the 07 February -18 February 2022at the Kenanga Poskesdes, Pal IX Village, Sub-district Sungai Kakap, District Kubu Raya. The sampling technique used non probability sampling, with sample is 15 pregnant women at third trimester. Measuring the degree of pain used the Faces Pain Scale Revised (FPS-R) questionnaire. The results of the study found that 74% were mothers aged 20-35 years, 67% had basic education, working mothers (87%), and multigravida (67%) The most common complaint experienced was moderate degree back pain with a total of 60% of respondents, this is what causes pregnant women to tire easily and requires treatment for this pain in the form of light exercise movements such as pregnancy exercise.